Combination of Sodium Butyrate and Immunotherapy in Glioma: regulation of immunologically hot and cold tumors via gut microbiota and metabolites - Li, Sui; Wang, Li; Han, MingYu; Fan, Huali; Tang, Hailin; Gao, Huile; Li, Guobo; Xu, Zheng; Zhou, Zhaokai; Du, JunRong; Peng, Cheng; Peng, Fu (Frontiers in Immunology, 2025)
BackgroundRecent studies have highlighted the importance of cross-talk along the gut-brain axis in regulating inflammatory nociception, inflammatory responses, and immune homeostasis. The gut microbiota, particularly its bacterial composition, plays a crucial role in the development and function of the immune system. Moreover, metabolites produced by the gut microbiota can significantly impact both systemic immune responses and central nervous system (CNS) immunity. Sodium butyrate is a key metabolite produced by the gut microbiota and, as a histone deacetylase inhibitor, can enhance the anti-tumor immunity of cytotoxic CD8+ T cells. However, it remains unclear whether sodium butyrate treatment can enhance the efficacy of PD-1 blockade in glioma therapy. In this research, the effect and underlying mechanism of combination of gut microbiota metabolites and anti-mouse PD-1 mAb on glioma has been investigated.MethodsRNA-seq assay in glioma cell and biomedical databases, including ONCOMINE, GEPIA and TCGA were incorporated. Subsequently, the inhibitory effect of sodium butyrate on glioma cells and its related mechanisms were assessed through Counting Kit-8 (CCK-8), Flow Cytometry, Western blot (WB), reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and other in vitro experiments. In vitro, an orthotopic mouse glioma model was established. MRI imaging, Immunohistochemistry, and Immune cell flow cytometry were used to investigate the therapeutic effects of combined sodium butyrate and PD-1 inhibitor treatment on glioma-bearing mice.ResultsWe discovered that deacetylation-associated gene expression is significantly increased in glioma patients and affects patient survival time. Moreover, we found sodium butyrate promoted glioma cell apoptosis, disrupted the cell cycle, and inhibited tumor growth. Additionally, sodium butyrate may upregulate PD-L1 expression in glioma cells by modulating the PI3K/AKT pathway. The experimental results demonstrated that this combination therapy significantly reduced tumor volume and prolonged survival in an orthotopic murine glioma model. Moreover, combination therapy led to an increase in the proportion of probiotic bacteria in the mouse gut microbiota, resulting in elevated levels of antitumor metabolites and a decrease in metabolites that affect immune cell function.